A New Technique for Reducing the Computational Complexity for 2D Mean Filters - Nguyen, Huu Tai (Old Journal, 2019)
Mean filters are among the most commonly used filters in the field of digital signal processing in general and image processing in particular. Therefore, the research and improvement of the filter technology will have a positive impact on both the hardware and the software. Our studies in this paper have shown a new implementation solution, which greatly improves computational complexity, thus reducing the time taken for implementation to be superior to that of the original technique. In experimental results in the form of software. In particular, these suggestions can naturally expand into the n-dimensional space.